Experimental Resonances in Viscoelastic Microfluidics - Vazquez-Vergara, Pamela; Torres-Herrera, Ulises; Caballero-Robledo, Gabriel A.; Olguin, Luis F.; Corvera Poiré, Eugenia (Frontiers in Physics, 2021)
Pulsatile flows of viscoelastic fluids are very important for lab-on-a-chip devices, because most biofluids have viscoelastic character and respond distinctively to different periodic forcing. They are also very important for organ-on-a-chip devices, where the natural mechanical conditions of cells are emulated. The resonance frequency of a fluid refers to a particular pulsatile periodicity of the pressure gradient that maximizes the amplitude of flow velocity. For viscoelastic fluids, this one has been measured experimentally only at macroscales, since fine tuning of rheological properties and system size is needed to observe it at microscales. We study the dynamics of a pulsatile (zero-mean flow) fluid slug formed by a viscoelastic fluid bounded by two air-fluid interfaces, in a microchannel of polymethyl methacrylate. We drive the fluid slug by a single-mode periodic pressure drop, imposed by a piezoactuator. We use three biocompatible polymer solutions of polyethylene oxide as model viscoelastic fluids, and find resonances. We propose a model accounting for surface tension and fluid viscoelasticity that has an excellent agreement with our experimental findings. It also provides an alternative way of measuring relaxation times. We validate the method with parameters reported in the literature for two of the solutions, and estimate the relaxation time for the third one.